Monographie der palaearktischen Lonchaeidae (Diptera). - Morge, Günter (Contributions to Entomology = Beiträge zur Entomologie, 1959)
Nomenclatural Actsappendiculus Morge, 1959 (Dasiops), spec. n.perpropinquus Morge, 1959 (Dasiops), spec. n.solivagus Morge, 1959 (Dasiops), spec. n.trichosternalis Morge, 1959 (Dasiops), spec. n.sericans Becker, 1895 (Lonchaea), Lectotype; syn. n. of Dasiops spatiosus (Becker, 1895)